Group Exhibition-A View to the Mediterranean Sea, The Cyprus Case Herzliya Artists’ Residency, Israel - Antoniou, Klitsa (My University, 2026)
A View to the Mediterranean Sea, The Cyprus Case Herzliya Artists’ Residency, Israel Curated by Ilan Wisgan